Life cycle assessment of desiccant – Dew point evaporative cooling systems with water reclamation for poultry houses in hot and humid climate. (25th June 2022) - Harrouz, Jean Paul; Katramiz, Elvire; Ghali, Kamel; Ouahrani, Djamel; Ghaddar, Nesreen
Graphical abstract: Highlights: A sustainable cooling system is proposed for poultry houses in hot and humid climate. It combines desiccant packed beds with a dew-point cooler and water reclamation unit. The system performance is evaluated for two desiccant types: silica gel and MOFs. The performance of each system was optimized to reduce the operation cost. The MOFs resulted in 27% reduction in the operating cost and 11-year payback period. Abstract: Desiccant – dew point evaporative based cooling systems is known to be an effective system for the ventilation and cooling of poultry houses in hot and humid climates. However, they suffer from high water consumption that hinders their application in desert regions. In this work, it is proposed to integrate a water reclamation unit with the cooling system to produce water from the adsorbent's humid regeneration stream. The performance of the hybrid cooling and water reclamation unit is evaluated for two desiccants: conventional (silica gel), which is cheap but has low water capacity, and novel (MIL-101-Cr, a type of metal organic framework), which is expensive but has high water capacity. The system was sized, and its operation was optimized using both adsorbents for a case study of a typical poultry house module located in the predominantly hot and humid climate of Qatar. This is achieved by developing numerical models for the different system's subcomponents, which are then validated with the published data. An artificial neural network was trained using the numerical model of water adsorption to accelerate the computational time of the genetic algorithm used for the performance optimization. A lifecycle cost comparative analysis is conducted to determine the integrated system most cost-effective adsorbent. Over the entire cooling season, it was found that the hybrid system using MIL-101-Cr resulted in 17% and 48% reduction in the thermal and electrical energy consumption compared to the one using silica gel. This has offered thus a 27% lower operating cost with a payback period of 11 years using the current market price of MIL-101-Cr.